Die probleem van die bereik van die ontkenning met spesiale verwysing na Afrikaans - Waher, Hester (University of Cape Town, 2016)
Since the formulation of the Katz-Postal Hypothesis Generative linguists have shown great interest in logical elements like quantifiers and negatives. Differences in the scope of these elements, which correspond to surface position, provide numerous counter examples to the thesis that all semantic information is represented in underlying structure. Part 1 of this study sketches the background of this problem and then examines critically the way in which two models of Generative Grammar, namely Interpretive and Generative Semantics, propose to account for the facts of the scope of negation. In Part 2 the correlation between the scope of negation and the distribution of Afrikaans negative particles is investigated. For the first negative particle this consists of testing its position and interpretation against the thesis generally held in linguistic theory that the leftmost logical element has the widest scope in the sentence. The results show that this particle functions to a considerable extent in the same way as the single negative of cognate languages like English and Dutch. It is argued that the Afrikaans negation differs from that of other standard Indo-European languages only in the presence of an additional negative element and that this element serves to mark the rightmost extent of the scope of negation. This hypothesis is also tested against the data and as a consequence the claim is made that it is well justified. The conclusion reached on the distributional facts is that they can be described in a simpler and more insightful way than has hitherto been done in Afrikaans grammar, if they are related to scope. In Chapter 8 the ability of the models of Generative and Interpretive Semantics to handle the facts of the Afrikaans negation is discussed. It is found that the highest degree of generalization can be achieved by the mechanisms provided by the former. It is therefore concluded that the Afrikaans negation supports the Generative rather than the Interpretive Semantics model.